Turk J Orthod 2022
DOI: 10.5152/turkjorthod.2022.21003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Cervical Vertebral Maturation Method: A Systematic Review

Abstract: Main Points• The aim of the study is to evaluate whether the cervical vertebral maturation (CVM) method is effective in terms of predicting the growth spurt. • Most of the previous studies have stated that the CVM method is an effective method for assessing skeletal maturity.• The CVM method and skeletal analysis of the hand-wrist method do not show significant differences.• No further radiographic investigations are required other than the lateral cephalogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(116 reference statements)
1
1
0
Order By: Relevance
“…5 According to the literature, CVM stages strongly correlate with skeletal maturity but some studies show a weak correlation. 11,18 The relation between left mandibular canine and skeletal maturation in the Pakistani population was 0.787 in this study. As a result, it may be concluded that the mandibular canine is an important factor in determining skeletal maturity.…”
Section: Discussionsupporting
confidence: 48%
“…5 According to the literature, CVM stages strongly correlate with skeletal maturity but some studies show a weak correlation. 11,18 The relation between left mandibular canine and skeletal maturation in the Pakistani population was 0.787 in this study. As a result, it may be concluded that the mandibular canine is an important factor in determining skeletal maturity.…”
Section: Discussionsupporting
confidence: 48%
“…Since it avoids additional exposure of the wrist to radiation, the CVM method has become a popular means of assessing skeletal maturity. Studies conducted in different countries and races have demonstrated the equivalent efficiency of using wrist bone analysis and CVM in predicting the growth peak of adolescents [7][8][9].…”
Section: Introductionmentioning
confidence: 99%